MENINGKATKAN KUALITAS INFORMASI AKUNTANSI MELALUI PEMBERDAYAAN APARATUR PEMERINTAH DALAM MEWUJUDKAN GOOD GOVERNANCE - Ikin Solikin Memen Kustiawan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
These days, citizens have grown to be very critical to government’s policies. They will challenge policies which they think inappropriate or irrelevant with their interests. This shift of values is a common process within developing communities. In response to this situation, the government is obliged to cater such a change through empowering citizens and administering a more accountable, transparent, feasible and participative governance. The government, in particular, should be liable for its performance by providing public finance accountability. This public finance accountability represents public transparency and accountable public sector managers. All these require local government capability to endow with accurate, relevant, and timely information of public accounting.